2008
DOI: 10.1159/000145324
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of Oral Anticoagulation after Acute Ischaemic Stroke or Transient Ischaemic Attack: Timing and Complications of Overlapping Heparin or Conventional Treatment

Abstract: Background: Oral anticoagulation is highly effective for secondary prevention of cardioembolic strokes in patients with atrial fibrillation (AF). There are no studies investigating timing and complications of different strategies for initiation of oral anticoagulation after acute stroke or transient ischaemic attack (TIA). Methods: Patients of ten community hospitals participating in the prospective evaluation of medical effects of the Telemedical Project for Integrative Stroke Care (TEMPiS) were included. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 44 publications
1
10
0
1
Order By: Relevance
“…First, hematoma growth and rebleeding beyond the 24-h time window after the initial event are less frequent in sICH compared to other ICH populations, e.g. ICH related to oral anticoagulant treatment [18,25,26,27] – Lim et al [19] reported significant hematoma growth (>50%) in 0.9% of sICH patients between days 2 and 7. Consistent with that study and similar findings reported previously [18], 2 out of the 97 patients analyzed here (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…First, hematoma growth and rebleeding beyond the 24-h time window after the initial event are less frequent in sICH compared to other ICH populations, e.g. ICH related to oral anticoagulant treatment [18,25,26,27] – Lim et al [19] reported significant hematoma growth (>50%) in 0.9% of sICH patients between days 2 and 7. Consistent with that study and similar findings reported previously [18], 2 out of the 97 patients analyzed here (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…614 The safety and efficacy of heparin, given as an interim therapy for those patients with atrial fibrillation who were beginning to receive oral anticoagulants, was evaluated in an observational study. 615 Heparin did not reduce the risk of thromboembolic events or increase the risk of bleeding complications, but the heparin bridging did prolong hospitalization. Besides an associated risk of bleeding, the administration of heparin to patients with acute ischemic stroke may be complicated by the development of heparininduced thrombocytopenia.…”
Section: Unfractionated Heparinmentioning
confidence: 99%
“…In many European hospitals, initial anticoagulatory treatment for these conditions is done with phenprocoumon and with bridging intravenous heparin until a therapeutic international normalized ratio (INR) has been reached [4]. This requires strict laboratory control of the very variable and clinically unpredictable individual treatment response.…”
Section: Introductionmentioning
confidence: 99%